Application of solubility parameters in the preparation of PMMA with permanent antistatic, high toughness, and excellent optical properties. (24th June 2021) - Chen, Si; Xu, Changbo; Ma, Meng; Shi, Yanqin; He, Huiwen; Yuan, Kaiyun; Xu, Ruqing; Wang, Xu
Abstract: In this paper, a novel kind of PMMA copolymer, P(MMA‐ co ‐MAA‐ co ‐SPMA), with permanently antistatic, high toughness, and high transparent properties, was synthesized via radical copolymerization. Herein, we selected the appropriate compatibilizer α‐methacrylic acid (MAA) and release agent (lauryldiethanolamine) through the calculation of solubility parameters for industrial mass production. What is more, the polymer's molecular weight was increased by improving the polymer's synthesis process. The structure and properties of the obtained copolymer were characterized. With 0.6 wt% of the 3‐sulfopropyl methacrylate potassium salt (SPMA), the copolymer exhibits nearly unchanged transparency with neat PMMA, and its unnotched impact strength reaches 16 kJ/m 2 . The surface resistance of the copolymer could be reduced to 10 10 Ω, which could be considered as antistatic materials. Finally, the antistatic mechanism was analyzed. The main reason is that the hydrophilic group absorbs water to form a conductive layer on the surface, and 3‐sulfopropyl methacrylate potassium salt (SPMA) is an ionic monomer that can form ion channels in water molecules, further accelerating the leakage of accumulated electrostatic charges and improving the antistatic properties of the copolymer. The method of selecting compatibilizers and release agents through solubility parameters provides more opportunities for the development of PMMA with excellent comprehensive performance.